The Literature Returning to ‘Tao’: A Thinking from Reading ‘El Jardín de Senderos que se Bifurcan’ - Zhang, Yi (Literary Studies, 2025)
‘El Jardín de senderos que se bifurcan’, the quintessential work of Argentine scribe Jorge Luis Borges, stands as a paragon of 20th-century Latin American Spanish literature. This narrative resonates profoundly with my scholarly sensibilities due to its striking alignment with the 'Yuan'ao' literary concept, a cornerstone of Chinese aesthetics, thereby enabling an interpretation of the short story through the lens of Chinese aesthetic principles. As a dedicated literary scholar, I have discerned a subtle yet profound layer of thought within ‘El Jardín de senderos que se bifurcan’, a layer that Borges endeavors to articulate. This stratum of thought is unveiled through meticulous textual juxtaposition and critical analysis. The articulation of these thoughts, in essence, masks a more profound ambition - the quest for 'Tao'. In the tapestry of traditional Chinese aesthetics, 'Tao' is revered as an eternal essence and the zenith of ontological inquiry, serving as the ultimate archetype that all creative endeavors, including literary works, aspire to emulate.My scholarly endeavor is anchored in the textual fabric of ‘El Jardín de senderos que se bifurcan’, enriched by a constellation of enlightening texts and a spectrum of concepts from Chinese aesthetic treatises. In the process of deconstructing and reconstructing its interpretation, I delve into the underlying concepts embedded within these discourses, aiming to unveil the ultimate pursuit of 'Tao'. I offer a novel perspective that seeks to ignite future dialogues on the cross-cultural dimensions of literary studies.